Supplementary file to: Carson, L. C. and Greenhill, K. (2015) One hat or many? A comparison of two models for the Copyright Officer position in university libraries, Library and Information Research, 39(121), 57-74. (2015) - Carson, L.C.; Greenhill, K.
No abstract available